Economic, environmental and social externalities of Tourism in Southeast Asia - Sherafatian-Jahromi, Reza (2016)
The Southeast Asian countries are highly dependable on their tourism industries and have set rising annual growths in tourist arrivals. According to World Tourist Organisation’s statistics, number of arrivals in this region in 2010 was four times higher than those in 1990. Malaysia, Indonesia, Singapore, Thailand, and Philippines are among the most important countries in this region. The positive sign of the five year average growth rate of tourist arrivals during 1981-2010, as well as the tourist receipts during 1996-2010 illustrated the importance of this sector.It is expected that tourist arrival growths in Southeast Asia would be around 5% annually till 2030. Consequently, it is extremely important to examine all aspects of this expansion. The present study tries to analyse the Southeast Asian countries tourism industry effects on the three pillars of sustainable development. In the case of the economic impact of tourism, income inequality and tourism relationship is examined. The environmental influence of tourism is assessed by considering the CO2 emissions and tourist nexuses. Finally, the social externality of tourism is appraised by having tourism and crime relationship.The impact of tourism on income inequality is assessed by applying the fixed effects model for static analysis as well as the dynamic fixed effect model for dynamic examination. The finding shows that tourism negatively affects the Gini index. In other words, this industry helps lower income people more than the rich and reduces the gap between the poor and the rich. Moreover, the dynamic relationship illustrates that speed of adjustment is highly ignificant and 67 percent of disequilibrium is corrected each year. Having the squared form of output in the model reveals the existence of Kuznets Curve in this region.There is an increasing concern that tourism highly affects the CO2 emissions. The linear and non linear relationship between tourism and CO2 emissions is tested, using the panel cointegration and pooled mean group techniques. The result indicates that tourism and CO2 emissions are cointegrated. Besides, tourism causes CO2 emissions in this region. Our findings support Tisdell (1987) in the case of the non linear relationship between tourism and emissions. The results lead to the conclusion that CO2 emissions, do reduce in high levels of arrivals. Moreover, this study confirms the existence of Environmental Kuznets Curve in Southeast Asia. Finally, the empirical results show that energy consumption highly affects the emissions.The static and dynamic relationship between tourism and crime is investigated by applying the random effects and fully modified ordinary least squares over the period 1980-2012. The long run relationship is approved by employing the unit root tests and cointegration test. The results of Hausman test revealed that random effect is preferred. The coefficient for tourist appears with the positive sign, showing that any tourism expansion increases the amount of crimes in Southeast Asia. Furthermore,the empirical results show that education and economic growth negatively affects crime. On the other side, unemployment rate and population have positively impact crime. Our dynamic examination indicates that the lagged form of crime significantly affects crime. In other words, crime is highly persistent.In spite of the positive effect of tourist arrivals on the economy, the negative externality of tourism in society should not be ignored. The simulation for 2020 and 2030 indicates that income inequality would reduce in the long run. High negative impact of GDP follows from the effects of tourism expansion, meanwhile,investment in education improves the income distribution. The CO2 emissions simulation shows that emissions in this region increase in 2020 and 2030, mostly because of the positive impact of energy consumption and GDP. Finally, crime simulation for 2020 and 2030 illustrates that investing more in education could cover the negative effects of tourism on crime. Overall, it can be concluded that the positive effects of tourism expansion in Southeast Asia are higher than their negative impact.